1992
DOI: 10.3346/jkms.1992.7.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the ventral rami of the brachial plexus

Abstract: We studied the variations in the ventral rami of 152 brachial plexuses in 77 Korean adults. Brachial plexus were composed mostly of the fifth, sixth, seventh and eighth cervical nerves and the first thoracic nerve (77.0%). In 21.7% of the cases examined, the fourth, fifth, sixth, seventh and eighth cervical and the first thoracic nerves contributed to the plexus. A plexus composed of the fourth, fifth, sixth, seventh and eighth cervical and the first and second thoracic nerves, and a plexus composed of the fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 0 publications
6
41
1
1
Order By: Relevance
“…In the surgical treatment of brachial plexus lesions, the surgeon must know brachial plexus anatomical variations perfectly. Common variations in the formation, prefixed and postfixed plexuses have been well documented (Matejcik, 2003a(Matejcik, , 2003b(Matejcik, , 2005Lee et al, 1992). Variations in the formation of the trunks of the brachial plexuses have also been reported (Matejcik, 2003b).…”
Section: Discussionmentioning
confidence: 94%
“…In the surgical treatment of brachial plexus lesions, the surgeon must know brachial plexus anatomical variations perfectly. Common variations in the formation, prefixed and postfixed plexuses have been well documented (Matejcik, 2003a(Matejcik, , 2003b(Matejcik, , 2005Lee et al, 1992). Variations in the formation of the trunks of the brachial plexuses have also been reported (Matejcik, 2003b).…”
Section: Discussionmentioning
confidence: 94%
“…Although the suprascapular artery was not quantified, it joined the suprascapular nerve in a neurovascular bundle fashion. The suprascapular nerve is a mixed sensory and motor peripheral nerve arising from the superior trunk of the brachial plexus (C5-C6) with a variable contribution from the fourth cervical nerve root [1,14]. We noted the suprascapular nerve to be in a vulnerable location as it tethers against the base of the acromion through the spinoglenoid notch and before entering the innervated infraspinatus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports state that the C7 and the C8 nerve roots have the largest ventral rami 18) , but others have reported that the largest are associated with the C6 and the C7 nerve roots 13) . Morphometrically, the BP is centered on the C4 nerve root and consists of the C5, C6, C7, and the C8 nerve roots.…”
Section: Discussionmentioning
confidence: 99%